JOURNAL OF A SOUL: A SOURCEBOOK OF THE SECOND VATICAN COUNCIL - O’Brien, Roderick (Asian Horizons, 2012)
Angelo Cardinal Roncalli, the Patriarch of Venice, had been elected Pope on 28 October 1958. He made his retreat a month later. Then in January 1959, he made the announcement which was to bring the winds of change to the Church: on 25 January he announced a Synod for the Diocese of Rome, and a Council for the Universal Church. The Synod for Rome took place over a few days in January 1960, while the Council began only in October 1962. It was to last much longer than the Synod.